Analysis Of The Management Of Productive Zakat At The Muhammadiyah, City Of Medan - AL Bara; Riyan Pradesyah (Proceeding International Seminar of Islamic Studies, 2019)
The purpose of this study is to look at the productive zakat fund system in the Muhammadiyah zakat institution in Medan. Management of zakat is currently still causing controversy. Where, the distribution of zakat funds is still less effective. Zakat management institutions show a lack of transparency and accountability in performance. The principle of justice is something that must be upheld.Where, justice in question is able to manage and distribute zakat funds appropriately and quickly. The implementation of zakat in alleviating poverty and improving the economy should be immediately relocated through improving the performance of the zakat institution itself. Because the role of zakat on the lives of the mustahik is very strategic if managed wisely.Developing productive zakat which is supposed to be one alternative in alleviating poverty, is now a funding given to the community. In fact, productive zakat is the provision of funds to mustahik or poor people, in economic development, not the provision of funding which must be returned to the zakat institution. So for that, here the researcher wants to see the concept of productive zakat giving at the Muhammadiyah zakat institute in Medan.This research will be carried out for 3 months and will conduct observations and conduct interviews directly at the Muhammadiyah Zakat Institute in Medan. To achieve the results of this research, this research uses a descriptive qualitative research method in which the researcher is directly involved actively meeting, observing, and interviewing participants to uncover the strategies of managing productive zakat in poverty alleviation, with a case study of the Muhammadiyah Zakat Institute, Medan City.